Potential of Antiprotons for Imaging and Radiotherapy - Giokaris, N.; Kalogeropoulos, Th. (HNPS Advances in Nuclear Physics, 2019)
The potential of antiprotons for nuclear imaging, chemical element identification and radiotherapy is examined. A comprehensive R&D program for the characterization of these techniques is outlined.